Late-Glacial Paleoecology of the Middle Susitna Valley, Alaska: Environmental Context for Human Dispersal - Bigelow, Nancy H.; Reuther, Joshua D.; Wallace, Kristi L.; Saulnier-Talbot, Émilie; Mulliken, Katherine; Wooller, Matthew J. (Frontiers in Earth Science, 2019)
We present here the results of multi-proxy analyses (sediment geochemistry, diatoms, and pollen) from sediment cores collected at four lakes in the middle Susitna Valley, Alaska. These lakes form a transect from the tundra to the boreal forest. The retrieved cores span from ∼12,000 cal yr BP to the present, with age control provided by radiometric dates and tephra deposits, some of which are newly identified. Results indicate that deglaciation occurred before 12,000 cal yr BP and that by that time, the lakes were deep, productive, and surrounded by shrub tundra. The lake with the highest sampling resolution indicates a brief climatic reversal ∼11,500 cal yr BP with decreased diatom-inferred lake level and lowered lake productivity, and reduced shrub presence. During the early to middle Holocene, all of the sedimentary records provide evidence of climatic amelioration with tree expansion and productive lakes. A middle to late Holocene climatic deterioration with reduced trees and a shallower, less productive lake is also indicated. In addition, the prominent Watana tephra at ∼4,000 cal yr BP likely reduced lake productivity and affected the vegetation. Even though the region was relatively productive soon after deglaciation, people did not occupy the region until ∼11,000 cal yr BP, about 1000 years later, and then only sparsely. By the middle and late Holocene, the region was more densely populated and this shift in human occupancy presumably reflects changes in resource abundance, especially caribou. Whether the Watana ashfall influenced caribou abundance and thus people, is still under investigation, but given the tephra’s effect on vegetation and lake productivity, it seems likely.